VD_FINDINFO Jug / 2020 / 478 vom 9. Juli 2020 - VD Tribunal cantonal (2020)
ACQUITTEMENT, PRÉSOMPTION D'INNOCENCE, ADMINISTRATION DES PREUVES, LÉSION CORPORELLE SIMPLE, ABUS D'AUTORITÉ | 6 CEDH, 10 CPP (CH), 147 al. 1 CPP (CH), 389 CPP (CH)